(untitled) (Indian Journal of Animal Production and Management, 2015)
One hundred and eighty (n=180) day old white commercial broiler chicks (Cobb 400) were randomly assigned to four treatment groups to study the effect of probiotics, prebiotic and synbiotics on growth performance of broilers. Birds were fed either basal diet only (CON) or the basal diet supplemented 500 g/tonne prebiotic (PRE), 100 g/tonne probiotic (PRO) or 500 g/tone prebiotic and 100 g/tonne probiotic (SYN). Average body weight gain (BWG), feed intake (FI), feed conversion ratio (FCR), mortality and cost of feeding of broilers were determined. Dietary supplementation with PRO and SYN had better (P<0.05) body weight as compared to CON and PRE-fed birds. BWG, FI, FCR and cost/kg live weight remained comparable (p>0.05) amongst different dietary treatment groups but the supplementation of probiotic had shown better gain as compared to other dietary treatments.